Signage effectivity in Soekarno-Hatta InternationalAirport Terminal 3 / Lalitya Talitha Pinasthika and Mohammad Rizaldi - Lalitya Talitha, Pinasthika; Mohammad, Rizaldi (Universiti Teknologi MARA, Perak, 2018)
Airport is the main entrance gate to visitors all across the world and it has to be provided with wayfinding to help passengers navigate themselves from one point to another. In 2017, the main airport in Indonesia, Soekarno-Hatta International Airport (SHIA) expanded its terminal and operated Terminal 3 to serve international flights from several airlines and also domestic flights specifically for Garuda Indonesia airlines only. To accommodate the needs to guide these passengers from one point to another, SHIA provided itself with airport wayfinding that were placed in all areas in many forms of signage. The propose of these signs are to guide passengers with different background, languages, and nationalities to find their ways inside the terminal building in unanimous understanding of the passenger flow without confusion. An initial research done by observing the all-access area in the departure and arrival floor, the finding indicated that some of the signage provided were misplaced and visually inconsistent from one and another, proved by the amount of visitor that still prefer to ask an officer on duty and also some make-shift signage made by printing paper that were placed in some key decision point areas by the airport authorities. Based on the initial research, further research initiated using qualitative methods by observing as the first person being the passenger that needs to navigate oneself from one point to another in four plots. This research aim is to analyse the effectivity of existed signage provided in SHIA to guide passengers in four different scenarios, involving departure and arrival in both international and domestic area of the terminal. By researching the effectivity of signage placement and information design system in SHIA, it becomes evident that passenger confusion applied mostly in arrival area in both international and domestic wings. The confusion appeared as the result of the misplaced signage, the visual inconsistency, the order of information provided in existing signage, and also the area that aren't well-lit in some vital points. This research proved the lack of information efficiency occurs in one of the busiest airport in Indonesia and it affected passenger flow, especially in arrival area on both international and domestic wings of the terminal.